Obinutuzumab-induced severe acute thrombocytopenia: a case report and literature review - Kou, Kun; Zhou, Qiaolin; Du, Lijun; Xu, Fang (Frontiers in Immunology, 2025)
Obinutuzumab is a humanized type II anti-CD20 monoclonal antibody that is widely used in B-cell lymphomas including follicular lymphoma (FL) and chronic lymphocytic leukemia (CLL). Multiple clinical studies have shown that compared with rituximab combined with chemotherapy, obinutuzumab combined with chemotherapy can significantly improve the progression-free survival (PFS) of patients, effectively reduce the risk of disease progression, and improve patient prognosis. The main adverse effects of obinutuzumab include infusion reactions, myelosuppression, infection, cardiotoxicity, tumor lysis syndrome (TLS), etc., and in rare cases it may induce thrombocytopenia. However, so far there are few reports on “obinutuzumab-induced acute thrombocytopenia” (OIAT), especially severe cases. Here, we report a case of acute severe OIAT and review the literature to explore the management of this rare but life-threatening complication. The case is a 28-year-old young man who was diagnosed with stage IV follicular lymphoma and achieved remission after 8 cycles of R-CHOP chemotherapy. Later, he developed severe acute thrombocytopenia during maintenance treatment with obinutuzumab monotherapy, the patient’s platelet count dropped from 191×10^9/L to 2×10^9/L on the 3rd day after the initial application, and severe thrombocytopenia occurred after multiple subsequent applications of obinutuzumab. OIAT is a rare but life-threatening complication. We should be aware of this adverse event and raise awareness about it.